Lessons Learned From the Implementation of an Integrated Health and Social Care Child and Family Hub – a Case Study - Sarah Loveday; Natalie White; Leanne Constable; Anthony Gates; Lena Sanci; Sharon Goldfeld; Harriet Hiscock (International Journal of Integrated Care)
Introduction: Childhood adversity is associated with poor physical and mental health outcomes across the lifespan. Integration of health and social care may provide a solution to childhood adversity through practices of better detection and response. There is growing interest in the creation of child and family hubs that integrate health and social care but little literature that describes the development process. Description: We aimed to evaluate and describe the implementation of a co-designed health and social care child and family hub in Victoria, Australia. Rapid ethnographic methodology was used to iterate the hub components. Practitioners and researchers co-created solutions to barriers identified during implementation. Discussion: There were five key learnings: (i) Practice change takes time and intensive coaching, (ii) Lived experience is a powerful motivator for practice change, (iii) Integration of services requires more than co-location to break down silos, (iv) Reflective practice is a key driver of practice change, and (v) Using real time data enabled rapid implementation change and directly informed the development of solutions. Conclusions: Maintaining and developing practice change during implementation requires time and access to a broad range of data to enable iteration and the development of solutions.